2022
DOI: 10.3390/ijerph19063731
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Patients with Pancreatic Cancer before and during the COVID-19 Pandemic

Abstract: Background: Coronavirus disease 19 (COVID-19) substantially affects cancer patients due to adverse outcomes and disruptions in cancer care. Recent studies have indicated the additional stress and anxiety burden arising from the pandemic and impairing quality of life in this vulnerable group of patients. However, patients with cancer represent a heterogenous group. Therefore, we conducted a study on patients with pancreatic cancer, requiring demanding surgical interventions and chemotherapy regimens due to its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Our sensitivity analyses showed contradictory findings in that those who completed the study during the COVID-19 pandemic reported the highest QOL while also being at higher risk for death. Other studies have reported negative impact of the COVID-19 pandemic on psychosocial QOL, 37 - 39 no impact on QOL, 40 , 41 or, similar to our study, a positive impact on QOL. 42 , 43 It can be hypothesized that the switch to virtual visits and reduced visits in hospital led to less treatment burden and higher QOL.…”
Section: Discussionsupporting
confidence: 88%
“…Our sensitivity analyses showed contradictory findings in that those who completed the study during the COVID-19 pandemic reported the highest QOL while also being at higher risk for death. Other studies have reported negative impact of the COVID-19 pandemic on psychosocial QOL, 37 - 39 no impact on QOL, 40 , 41 or, similar to our study, a positive impact on QOL. 42 , 43 It can be hypothesized that the switch to virtual visits and reduced visits in hospital led to less treatment burden and higher QOL.…”
Section: Discussionsupporting
confidence: 88%
“…Differences in physical and psychological well-being were not significantly lower than before the pandemic time, while social well-being was significantly lower. Similarly, the results of research conducted by Alexander et al [27] showed that there is no significant difference in the physical condition of cancer patients before and during Covid-19 that is unlike the case with a decrease in social functions, roles, and emotions which differ before and during COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 84%
“…However, continuous follow-ups should be processed to further observe in a long term. Some studies proposed that the COVID-19 could impair the prognoses of pancreatic cancer patients, 21,22 which probably resulted from the impaired cancer screening, diagnosis, and care. 23 The vaccination was not discovered associated with the OS of PAC patients.…”
Section: Discussionmentioning
confidence: 99%